Self-Measure Office Blood Pressure (SMOBP) and Home Blood Pressure Monitoring (HBPM) for white coat effect diagnosis among hypertension patients - Pavornpath Burimsittichai; Tatree Bosittiphichet; Thanakamon Leesri (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: Hypertension is a critical factor in the deaths over the world among those who have cardiovascular diseases such as coronary artery disease, stroke, and chronic kidney disease.Purpose: This study aims to investigate the diagnosis capability of the white coat effect in hypertensive patients whose blood pressure was not on target.Methods: This study is an analytical study. Data were collected from 19 uncontrolled hypertension patients at Bang Si Thong health promoting hospital from August to December 2022. The geographic data are presented in the descriptive statistic terms of mean, difference, and standard deviation. The research outcome was analyzed by paired t-test.Results: The research results showed blood pressure measurement by SMOBP was more valuable in terms of statistical significance than Daytime HBPM (134±8.21 vs 125.5±6.74 p<0.001), while it was statistically significantly lower than Office-measured (148.15±10.33 vs 134±8.21 p<0.001), and there were participants whose blood pressures were going as a targeted by SMOBP 55% and HBPM 80%.Conclusion: Self-Measure Office Blood Pressure [SMOBP] can eliminate some of the white coat effect, but it could not be used instead of Home Blood Pressure Monitoring [HBPM] for the diagnosis of white coat hypertension. The SMOBP might be a choice for patients who have the white coat effect in socioeconomically disadvantaged areas.